Mediation of the positive chronotropic effect of CGP 12177 and cyanopindolol in the pithed rat by atypical beta-adrenoceptors, different from beta 3-adrenoceptors. - Malinowska, B. (1996)
1. The influence of beta 1-, beta 2-, and beta 3-adrenoceptor agonists and of CGP 12177 and cyanopindolol on heart rate and diastolic blood pressure was studied in the pithed rat. 2. The beta 1-adrenoceptor agonist, prenalterol, increased heart rate and the beta 2-adrenoceptor agonist, fenoterol, caused a fall in blood pressure. The effect of prenalterol was antagonized by the beta 1-adrenoceptor antagonist, CGP 20712 0.1 mumol kg-1 and the action of fenoterol was attenuated by the beta 2-adrenoceptor antagonist, ICI 118551 0.1 mumol kg-1. Both effects were markedly diminished by the non-selective beta-adrenoceptor antagonist, bupranolol 0.1 mumol kg-1. 3. The non-selective beta-adrenoceptor agonist, isoprenaline, three beta 3-agonists as well as CGP 12177 and cyanopindolol elicited a positive chronotropic effect, exhibiting the following pED delta 60 values (negative log values of the doses increasing heart rate by 60 beats min-1): isoprenaline 10.4, CGP 12177 8.3, cyanopindolol 7.2, BRL 37344 6.9, ZD 2079 5.2 and CL 316243 < 5. 4. CGP 20712 0.1 mumol kg-1, given together with ICI 118551 0.1 mumol kg-1, markedly attenuated the positive chronotropic effect of isoprenaline, BRL 37344, ZD 2079 and CL 316243 without affecting the increase in heart rate produced by CGP 12177 and cyanopindolol. 5. The positive chronotropic effect of CGP 12177 and cyanopindolol was attenuated by CGP 20712, 1 and 10 mumol kg-1 and bupranolol, 10 mumol kg-1 but was not affected by ICI 118551, 10 mumol kg-1. The effect of CGP 12177 was also not changed by BRL 37344 1 mumol kg-1, ZD 2079 10 mumol kg-1, CL 316243 10 mumol kg-1, the alpha 1-adrenoceptor antagonist, prazosin 1 mumol kg-1 and the 5-hydroxytryptamine 5-HT2A receptor antagonist, ketanserin 3 mumol kg-1. 6. CGP 12177 0.002 mumol kg-1 and cyanopindolol 0.003 mumol kg-1 shifted to the right the dose-response curve of prenalterol for its positive chronotropic effect. The -log values of the doses causing a twofold shift to the right were 9.6 and 9.5, respectively. 7. Isoprenaline 0.00001-0.001 mumol kg-1, BRL 37344 0.01-1 mumol kg-1 and CGP 12177 0.1 mumol kg-1 caused a fall in diastolic blood pressure which was markedly attenuated by combined administration of CGP 20712 and ICI 118551, 0.1 mumol kg-1 each. 8. CGP 12177 0.01 and 0.1 mumol kg-1 and cyanopindolol 1 mumol kg-1 elicited an increase in diastolic blood pressure. CGP 20712, ICI 118551, bupranolol and, in the case of CGP 12177, also BRL 37344, ZD 2079, CL 316243, prazosin and ketanserin did not influence this effect. 9. In conclusion, the positive chronotropic effect of CGP 12177 and cyanopindolol is not mediated via beta 1-, beta 2-, beta 3-, alpha 1-adrenoceptors or 5-HT2A receptors. This effect may involve atypical beta-adrenoceptors, similar or identical to those described by Kaumann (1989) in isolated heart preparations.